FixItFelix: improving genomic analysis by fixing reference errors - Behera, Sairam; LeFaive, Jonathon; Orchard, Peter; Mahmoud, Medhat; Paulin, Luis F.; Farek, Jesse; Soto, Daniela C.; Parker, Stephen C. J.; Smith, Albert V.; Dennis, Megan Y.; Zook, Justin M.; Sedlazeck, Fritz J. (Genome Biology, 2023)
The current version of the human reference genome, GRCh38, contains a number of errors including 1.2 Mbp of falsely duplicated and 8.04 Mbp of collapsed regions. These errors impact the variant calling of 33 protein-coding genes, including 12 with medical relevance. Here, we present FixItFelix, an efficient remapping approach, together with a modified version of the GRCh38 reference genome that improves the subsequent analysis across these genes within minutes for an existing alignment file while maintaining the same coordinates. We showcase these improvements over multi-ethnic control samples, demonstrating improvements for population variant calling as well as eQTL studies.